An Investigation into Teachers’ Attitudes towards and Practices of Corrective Feedback on Students’ Oral Mistakes at Hanoi National University of Education = Nghiên cứu thái độ và thực tiễn việc sửa lỗi cho sinh viên trong kỹ năng nói của giáo viên tại trường Đại học Sư phạm Hà Nội - Đinh, Thị Hương (2020)
This minor research investigated the relationship between the attitudes and teaching practices of corrective feedback among a number of teachers of English. Participants were those who were teaching English as a foreign language in Hanoi National University of Education with certain years of teaching experience. The method to be employed was a survey questionnaire which involved 30 lecturers. This was followed by the researcher’s classroom observation of 12 lessons by three teachers chosen from the participants from the survey. They were teaching speaking skill for English majors in the same faculty at the university. T1 was in charge of a class with 37 sophomores, T1 with 28 juniors and T3 with 32 seniors. Finally, one-to-one informal interviews were administered in a semi-structured format with these three teachers. Accordingly, the data were collected both quantitatively and qualitatively through a procedure of note-taking, then combining with the results from informal interviews. The process of data collection was carried out during the first four weeks of the first semester, academic year 2012-2013. The findings revealed both differences and similarities between participants’ attitudes towards error treatment and their practical application in their speaking classroom settings.